Trefftz type approximation and the generalized finite element method - history and development - Zienkiewicz, Olgierd C. (Computer Assisted Methods in Engineering and Science, 1997)
This paper shows the essential unity between the known approximation procedures to differential equations. The boundary type approximations associated with Trefftz are shown to be a particular form of the weighted residual approximation and can provide a very useful basis for generating hybrid ’finite elements’. These can be used in combination with other finite element approaches.